Improved microbial electrolysis desalination and chemical-production cell for a high-value product: Hydrogen peroxide. Issue 3 (June 2022) - Li, Huankai; Liu, Hui; Lin, Weizhong; Huang, Weibao; Li, Jinjin; Bi, Jiawei; Ye, Bo
Abstract: A high-value product of microbial electrolysis desalination and chemical-production cell (MEDCC) is a promising method for reducing costs and broadening the cell's application. This study proposed a modified MEDCC in terms of hydrogen peroxide (H2 O2 ) production, electrochemical performance, desalination, energy consumption by comparing it with conventional MEDCC. At the optimal voltage (1.0 V), the improved system achieved the H2 O2 concentration of 1183 ± 32 mg/L, the energy consumption of 8.42 ± 1.39 kWh/kg H2 O2, the desalination efficiency of 60.36 ± 9.24% within 12 h. Although the MEDCC-H2 O2 system had a lower transfer rate of electrons, the system had analogous performances on current density, desalination, and acid and alkali productions with the conventional system. These results meant that the ideal voltage for achieving bipolar membrane and electrochemically active bacteria (EAB) synergism was 1.0 V in the improved MEDCC. In terms of chemical production in the cathode chamber of the MEDCC, the application of H2 O2 production increased the rate of return by four times when compared to conventional alkali production. Only about 55% of total consumption was attributed to bioenergy in the substrate, suggesting the system was energy-saving. Therefore, the revised MEDCC had great potential in the field of energy-efficient and green H2 O2 generation and desalination whilst maintaining acid and alkali productions. Graphical Abstract: ga1 Highlights: Simultaneously H2 O2 generation and desalination first appeare in MEDCC. The rate of return for H2 O2 generation increases by 4 times for alkali production. About 55% of total energy consumption comes from bioenergy. The optimal voltage to achieve synergism between biopolar membrane and EAB is 1.0 V. The mechanism, advantage, and prospect of the MEDCC-H2 O2 system are discussed.